The Effect of Catechin on Fungal Biofilm Formation of Standard Susceptible and Resistant Strains of Candida albicans - F Haghighi; SH Roudbar Mohammadi; Z Farhadi (Armaghane Danesh Bimonthly Journal, 2011)
Background & Aim: Candida albicans is the most common cause of fungal infections which is increasing all over the world. Finding new methods or agents for control of these fungal infections is necessary. The aim of this study was to evaluate the antifungal activity of Catechin against standard strain of C.albicans.